Anatomical features of the phytotelma dwelling, egg‐eating, fanged tadpoles of Rhacophorus vampyrus (Anura: Rhacophoridae). (17th March 2021) - Vera Candioti, Florencia; dos Santos Dias, Pedro Henrique; Rowley, Jodi J. L.; Hertwig, Stefan; Haas, Alexander; Altig, Ronald
Abstract: Tadpoles of the Vampire tree frog Rhacophorus vampyrus differ substantially from other rhacophorid tadpoles, by having profound modifications in external morphology. The morphological peculiarities of this species likely correlate with their arboreal microhabitat and strict oophagous diet. In this work, we examine buccal and musculoskeletal anatomy and compare them to other rhacophorid and egg‐eating larvae. The shape and arrangement of cartilages of the lower jaw are unique among tadpoles, and the lack of a palatoquadrate suspensorium is only known in the distantly related macrophagous tadpoles of the dicroglossid Occidozyga baluensis . The cranial musculature is massive, and the morphology of several mandibular, hyoid, and abdominal muscles could be related to the ingestion and transit of large eggs. In the buccal cavity, conspicuous aspects are the absence of ridges and papillae, and the development of a unique glandular zone in the buccal floor. Finally, observations of the skeletal support of keratinized mouthparts allow us to present a topography‐based hypothesis of homology of the conspicuous fangs of these tadpoles. Abstract : Unique anatomical features of the fanged tadpoles of Rhacophorus vampyrus, including infrarostral cartilages supporting fangs, a lack of the palatoquadrate suspensorium, and massive branchial musculature.